Arterial Obstruction on Computed Tomographic or Magnetic Resonance Angiography and Response to Intravenous Thrombolytics in Ischemic Stroke. Issue 2 (February 2017) - Mair, Grant; von Kummer, Rüdiger; Adami, Alessandro; White, Philip M.; Adams, Matthew E.; Yan, Bernard; Demchuk, Andrew M.; Farrall, Andrew J.; Sellar, Robin J.; Sakka, Eleni; Palmer, Jeb; Perry, David; et al.
Abstract : Background and Purpose—: Computed tomographic angiography and magnetic resonance angiography are used increasingly to assess arterial patency in patients with ischemic stroke. We determined which baseline angiography features predict response to intravenous thrombolytics in ischemic stroke using randomized controlled trial data. Methods—: We analyzed angiograms from the IST-3 (Third International Stroke Trial), an international, multicenter, prospective, randomized controlled trial of intravenous alteplase. Readers, masked to clinical, treatment, and outcome data, assessed prerandomization computed tomographic angiography and magnetic resonance angiography for presence, extent, location, and completeness of obstruction and collaterals. We compared angiography findings to 6-month functional outcome (Oxford Handicap Scale) and tested for interactions with alteplase, using ordinal regression in adjusted analyses. We also meta-analyzed all available angiography data from other randomized controlled trials of intravenous thrombolytics. Results—: In IST-3, 300 patients had prerandomization angiography (computed tomographic angiography=271 and magnetic resonance angiography=29). On multivariable analysis, more extensive angiographic obstruction and poor collaterals independently predicted poor outcome ( P <0.01). We identified no significant interaction between angiography findings and alteplase effect on Oxford Handicap Scale ( P ≥0.075) in IST-3. In meta-analysis (5 trials of alteplase or desmoteplase, including IST-3, n=591), there was a significantly increased benefit of thrombolytics on outcome (odds ratio>1 indicates benefit) in patients with (odds ratio, 2.07; 95% confidence interval, 1.18–3.64; P =0.011) versus without (odds ratio, 0.88; 95% confidence interval, 0.58–1.35; P =0.566) arterial obstruction ( P for interaction 0.017). Conclusions—: Intravenous thrombolytics provide benefit to stroke patients with computed tomographic angiography or magnetic resonance angiography evidence of arterial obstruction, but the sample was underpowered to demonstrate significant treatment benefit or harm among patients with apparently patent arteries. Clinical Trial Registration—: URL:http://www.isrctn.com . Unique identifier: ISRCTN25765518. Abstract : Supplemental Digital Content is available in the text.